Typhoon- and temperature-induced quasi-static responses of a supertall structure. (15th July 2017) - Su, J.Z.; Xia, Y.; Zhu, L.D.; Zhu, H.P.; Ni, Y.Q.
Highlights: Temperature- and wind-induced quasi-static responses are separated and compared. Canton Tower is investigated using a comprehensive real-time structural monitoring system. Measured typhoon-induced displacement is compared with the results of the wind tunnel test. Abstract: Wind loads and the associated load effects on supertall structures are key factors in structural design. In practice, typhoon-induced quasi-static responses measured from the field mix with temperature-induced responses because temperature varies significantly during a typhoon event. The mixed responses complicate the assessment of the wind loading effects and the separation of the two load effects is difficult in practice. In this study, the wind- and temperature-induced quasi-static responses of the 600 m-tall Canton Tower are investigated using a comprehensive long-term structural monitoring system installed on the structure. The structural responses (stresses and displacement) obtained from the field monitoring system during a strong typhoon are presented. The temperature-induced responses are calculated by applying a temperature loading model to the finite element model of the structure. The purely typhoon-induced quasi-static responses are then separated from the total measured responses by subtracting the temperature-induced ones. It shows that the typhoon-induced quasi-static responses of the supertall structure are slightly smaller than the temperature-induced responses in a typical sunny day. The typhoon-induced quasi-static displacement obtained from the field is also compared with the counterpart from the wind tunnel test on an aeroelastic model of the full tower.